Solze za Hekubo - Verč, Ivan (Slavistična revija, 1997)
In Russian literature the reception of Hamlet as a literary character and of Shakespeare as stage director depends on the special culturological status of intertextuality. The Russian writer needs a "foreign" model as a confirmation of "his own" world: in Hamlet's words Dostoevsky discovers the falseness of life, based only on the image of reality expressed in words ("the tears for Hecuba"); Turgenev needs a Shakespearean character to complement Russian "Don Quixotes"; Tolstoy's entirely negative attitude towards Shakespeare can be understood as a demand for the "spiritualization" of society originating in the peasant and religious consciousness ot the Russian people.
Keywords: angleška dramatika; Dostoevskij, Fedor Mihajlovič, 1821-1881; literarne študije; literarni vplivi; ruska književnost; Russian literature; Shakespeare, William, 1564-1616; Shakespeare, William: Hamlet; Tolstoj, Lev Nikolaevič, 1820-1910; Turgenev, Ivan Sergeevič